Research and Advanced Technology for Digital Libraries International Conference on Theory and Practice of Digital Libraries, TPDL 2013, Valletta, Malta, September 22-26, 2013. Proceedings - Aalberg, Trond; Papatheodorou, Christos; Dobreva, Milena; Tsakonas, Giannis; Farrugia, Charles J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the International Conference on Theory and Practice of Digital Libraries, TPDL 2013 (formerly European Conference on Research and Advanced Technology for Digital Libraries, ECDL) held in Valletta, Malta, in September 2013. The 24 full papers, 13 short papers, 22 posters and 8 demonstrations presented in this volume were carefully reviewed and selected from 158 submissions. The papers cover a wide range of research topics, clustered in four broader ares: foundation, infrastructures, content, and services. They have been organized in topical sections on conceptual models and formal issues, aggregation and archiving, user behavior, digital curation, mining and extraction, architectures and interoperability, interfaces to digital libraries, semantic web, information retrieval and browsing, and preservation. Also included are 6 tutorials and 2 panels.
Conceptual models and formal issues -- Aggregation and archiving -- User behavior -- Digital curation -- Mining and extraction -- Architectures and interoperability -- Interfaces to digital libraries -- Semantic web -- Information retrieval and browsing -- Preservation.
Keywords: Computer science; Information systems; Artificial intelligence; Text processing (Computer science; Computer Science; Document Preparation and Text Processing; Information Systems and Communication Service; Artificial Intelligence (incl. Robotics).